Family Compliance With Counseling for Children Traveling to the Tropics. Issue 3 (8th March 2013) - Caillet‐Gossot, Stéphanie; Laporte, Rémi; Noël, Guilhem; Gautret, Philippe; Soula, Georges; Delmont, Jean; Faucher, Benoit; Parola, Philippe; Osei, Lindsay; Minodier, Philippe
<x xml:space="preserve">Abstract</x> Background The number of people, both adults and children, traveling abroad, is on the rise. Some seek counseling at travel medicine centers before departure. Methods A prospective study was conducted among children <16 years visiting a travel medicine center in Marseille, France, from February 2010 to February 2011. Parents were contacted by telephone 4 weeks after their return, and asked about compliance with pre‐travel advice. Results One hundred sixty‐seven children were evaluated after their trip. Compliance with immunizations, malaria chemoprophylaxis, and food‐borne disease prevention was 71, 66, and 31%, respectively. Compliance with malaria chemoprophylaxis varied significantly with destination, and was higher for African destinations. Significant features associated with poor compliance with chemoprophylaxis were a trip to Asia or the Indian Ocean, age <5 years, and a monoparental family. Compliance with prevention of food‐ and water‐borne diseases was higher in children < 2 years of age. Conclusions A ≥80% compliance with pre‐travel counseling in children traveling overseas was achieved only for drinking bottled water, using repellents, a routine vaccine update, and yellow fever immunization.